2010
DOI: 10.1111/j.1398-9995.2009.02222.x
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation/fibrinolysis and inflammation markers are associated with disease activity in patients with chronic urticaria

Abstract: The measurement of plasma FDP, d-dimer and serum CRP may be useful for the assessment of disease activity of CU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
141
3
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(160 citation statements)
references
References 23 publications
13
141
3
3
Order By: Relevance
“…Chronic urticaria is frequently characterized by the presence of elevated levels of plasma markers of thrombin generation and fibrinolysis during severe exacerbations of the disease (37,38,47), which can be due to the expression of TF by activated eosinophils (22). The activation of coagulation and fibrinolysis decreases till complete normalization during remission (47,89). Whether the activation of coagulation/ fibrinolysis has a main role in the pathogenesis of the disease or simply acts as an amplification system has still to be defined.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic urticaria is frequently characterized by the presence of elevated levels of plasma markers of thrombin generation and fibrinolysis during severe exacerbations of the disease (37,38,47), which can be due to the expression of TF by activated eosinophils (22). The activation of coagulation and fibrinolysis decreases till complete normalization during remission (47,89). Whether the activation of coagulation/ fibrinolysis has a main role in the pathogenesis of the disease or simply acts as an amplification system has still to be defined.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that there should be possible role of clotting factors in flaring symptoms induced by autologous plasma, because autoantibodies are equally present in serum and plasma [35]. Also, a statistically significant relationship between elevated plasma levels of PF1+2 and D-dimer and the severity of CSU was reported in some studies [36,37].…”
Section: Comorbidities and Possible Triggering Factorsmentioning
confidence: 90%
“…Although the exact role of the activation of coagulation/ fibrinolysis in the pathogenesis of CSU has still to be defined, the fact that such an activation parallels the activity of the disease [11,47] provides theoretically a rationale to test effects of anticoagulant and antifibrinolytic therapy in patients with severe forms. A small double-blind, placebo-controlled study carried out about 15 years ago first detected the effectiveness of oral anticoagulant therapy in some patients with refractory CSU [48].…”
Section: Anticoagulants/antifibrinolytics In Chronic Spontaneous Urtimentioning
confidence: 99%